Estudo da qualidade dos recursos hídricos no estado do Ceará: uma abordagem inovadora - França, Josefa Marciana Barbosa de (2021)
The construction of infrastructure to transport water between hydrographic basins and the exploitation of underground water become necessary, due to the increase in the demand for water to meet population growth and other categories of uses. And to mitigate conflicts over use and avoid and reduce waste, it is necessary to manage these scarce and limited resources in nature. From the analysis of quantitative and qualitative monitoring, using multivariate statistical tools, both referenced in this thesis; concomitantly with the resource management instruments, provided for in the state legislation of Ceará and other legal frameworks, the aim is to contribute to a more efficient management of the system under analysis. It was found from the analysis of the granting processes that the flow of crystalline aquifers, the average is 1.20 L.s-1, and in the sedimentary subsoil, 4.27 L.s-1, intended mainly for irrigation, human supply and industry. It was also found that 69% of grant applications in 2017 were for abstraction in groundwater. However, the predominance in 73% of the flows granted was captured from surface sources. It was identified that the accelerated eutrophication process occurs from upstream to downstream in the SCRMF, where the proliferation of cyanobacteria within the Integration channel has been identified. The release of flows through the hypolimnetic layer of the Castanhão reservoir contributes to high loads of nitrogen and phosphorus, which fluctuate according to the flow rate operated by the monitoring system, as well as causing deoxygenation for a length of 43.50 km downstream in the Canal. The high temperatures (maximum: 33.64 ºC, minimum: 27.27 ºC) identified in the Integração canal, also contribute to maintaining the system with high densities of cyanobacteria, whose predominance represented more than 93% of phytoplankton, with a total of 38 taxa of cyanobacteria, whose dominant genera in the SCRMF were: Oscillatoria sp. and Microcystis sp., and the others identified as abundant: Merismopedia sp., Cylindrospermopsis sp., Pseudanabaena sp., Anabaena sp., Aphanizomenon sp., Aphanocapsa sp., Dolichospermum sp., Planktothrix sp., Raphidiopsis sp. In general, it was found that the Gavião reservoir underwent a greater magnification of the eutrophication process, as it quantified a higher density of cyanobacteria, with predominance in the stratified water period. It was also possible to identify that there was a seasonal thermal stratification in the Castanhão and Gavião reservoirs, with a stratification process in the first semester, and remained unstratified in the second semester.